On the Borda-Kendall Consensus Method for Priority Ranking Problems - Cook, Wade D.; Seiford, Lawrence M. (Management Science, 1982)
This paper investigates the Borda-Kendall method for the determination of a consensus ranking. It is shown that in the case of ties the method does not perform as claimed. A “minimum variance” method for determining the consensus ranking is proposed and its properties examined. It is shown to be equivalent to the Borda-Kendall method if ties are not allowed. An algorithm to determine the “minimum variance” consensus ranking in the case of ties is described. Results obtained from the solution of problems of various sizes are discussed.